2021
DOI: 10.1177/0036933021994264
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of injury following equine trauma: a non-trauma centre experience

Abstract: Introduction Horse riding carries risk of injury which can result in fatality. The majority of published literature describes major trauma centre experience. We aimed to characterise injury patterns following equine trauma at a Scottish district general hospital. Methods A retrospective review of admissions following equine trauma was undertaken from 2014 to 2019. Mechanism and nature of injuries were noted. Patient management and outcomes were recorded and analysed to determine correlation. Results Of the 162… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…Our results demonstrate that this group of patients is dominated by the female sex, has a heavy majority of patients who are under the age of 18, and most commonly sustain injuries due to falling off the horse. These findings are corroborated by other studies [ 3 , 15 , 16 ]. Although mortality and the need for intensive care in the total cohort were very low at 0.03% and 1.2%, respectively, 24.9% of the cohort required hospital admission.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results demonstrate that this group of patients is dominated by the female sex, has a heavy majority of patients who are under the age of 18, and most commonly sustain injuries due to falling off the horse. These findings are corroborated by other studies [ 3 , 15 , 16 ]. Although mortality and the need for intensive care in the total cohort were very low at 0.03% and 1.2%, respectively, 24.9% of the cohort required hospital admission.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, of all the equestrian related injuries from the admitted subgroup, 43.3% (n = 328) required surgery. Other publications on equine trauma have found similar, or even higher, surgical rates ranging between 24% and 50% [ 4 , 16 , 30 ]. This indicates that injuries sustained in equestrian sports require surgery more frequently than those from many other sports.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The type of data available and the methods of data collection also influence consistent reporting. Despite this, four studies reported a decrease in horse trauma over their study periods [ 19 , 21 , 22 , 36 ], one reported no change [ 39 ], and Jones et al [ 7 ] reported a slight non-significant annual increase. A recent assessment of fatal incidents on Australian farms involving children (2001–2019) found that horses were the agent of injury in 5.4% of cases [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common mechanism of injury was a fall from a horse, with the proportion ranging from 45.1 to 86.4% of all mechanisms [ 36 , 41 ]. Equestrians who had fallen had the highest injury scores, were most likely to be admitted to hospital, had the most diagnostic imaging performed, and tied with horse kick injuries for the longest mean hospital stay [ 6 ].…”
Section: Resultsmentioning
confidence: 99%